Payment mechanism for institutional births in Nepal - Ashish KC; Mats Målqvist; Amit Bhandari; Rejina Gurung; Omkar Basnet; Avinash K Sunny (BMC, 2021)
Abstract Background Since the Millennium Development Goal era, there have been several efforts to increase institutional births using demand side financing. Since 2005, Government of Nepal has implemented Maternity Incentive Scheme (MIS) to reduce out of pocket expenditure (OOPE) for institutional birth. We aim to assess OOPE among women who had institutional births and coverage of MIS in Nepal. Method We conducted a prospective cohort study in 12 hospitals of Nepal for a period of 18 months. All women who were admitted in the hospital for delivery and consented were enrolled into the study. Research nurses conducted pre-discharge interviews with women on costs paid for medical services and non-medical services. We analysed the out of pocket expenditure by mode of delivery, duration of stay and hospitals. We also analysed the coverage of maternal incentive scheme in these hospitals. Results Among the women (n-21,697) reporting OOPE, the average expenditure per birth was 41.5 USD with 36 % attributing to transportation cost. The median OOPE was highest in Bheri hospital (60.3 USD) in comparison with other hospitals. The OOPE increased by 1.5 USD (1.2, 1.8) with each additional day stay in the hospital. There was a difference in the OOPE by mode of delivery, duration of hospital-stay and hospital of birth. The median OOPE was high among the caesarean birth with 43.3 USD in comparison with vaginal birth, 32.6 USD. The median OOPE was 44.7 USD, if the women stayed for 7 days and 33.5 USD if the women stayed for 24 h. The OOPE increased by 1.5 USD with each additional day of hospital stay after 24 h. The coverage of maternal incentive was 96.5 % among the women enrolled in the study. Conclusions Families still make out of pocket expenditure for institutional birth with a large proportion attributed to hospital care. OOPE for institutional births varied by duration of stay and mode of birth. Given the near universal coverage of incentive scheme, there is a need to review the amount of re-imbursement done to women based on duration of stay and mode of birth.